2018
DOI: 10.1002/pbc.26940
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of response, progression‐free survival, and overall survival using NANT Response Criteria (v1.0) in relapsed and refractory high‐risk neuroblastoma

Abstract: NANTRCv1.0 response of at least SD is associated with better OS in patients with recurrent/refractory neuroblastoma. Patient and tumor characteristics may predict response and outcome. Identifying these variables can optimize Phase 1/2 trial design to select novel agents for further testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Many studies have shown that MYCN is an independent factor for unfavorable prognosis. [ 11 12 ] The key action of MYCN in inducing NB has been confirmed in vivo and in vitro. [ 13 14 ] The number of MYCN copies required to be defined as amplification is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that MYCN is an independent factor for unfavorable prognosis. [ 11 12 ] The key action of MYCN in inducing NB has been confirmed in vivo and in vitro. [ 13 14 ] The number of MYCN copies required to be defined as amplification is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for an inferior outcome included stage 4, age ≥18 months at first diagnosis, MYCN amplification, loss of heterozygosity of chromosome 11q, shorter time from diagnosis to first recurrence, abdominal primary tumor, bone marrow metastasis at first diagnosis, recurrent disease (vs refractory disease), and increased lactate dehydrogenase blood levels . Other predictors for poor outcome were measurable tumor on computed tomography/ magnetic resonance imaging at second‐line trial enrollment, high Curie score by metaiodobenzylguanidine scintigraphy, and stem cell supported therapy . The analyzed cohorts varied and included recurrences from localized tumors, patients aged less than 18 months at diagnosis, and patients with refractory disease …”
Section: Introductionmentioning
confidence: 99%
“…Other predictors for poor outcome were measurable tumor on computed tomography/ magnetic resonance imaging at second‐line trial enrollment, high Curie score by metaiodobenzylguanidine scintigraphy, and stem cell supported therapy . The analyzed cohorts varied and included recurrences from localized tumors, patients aged less than 18 months at diagnosis, and patients with refractory disease …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations